CINTA RUPIAH: EDUKASI UANG DAN PENGELOLAANNYA BAGI SISWA SEKOLAH DASAR - Liana Dewi; Revalina Yunijar; Via Fitriani (Jurnal Bakti kepada Masyarakat, 2025)
The inability to manage finances well often stems from a lack of financial literacy. Millennials and Generation Z face low financial literacy, which has a significant impact on economic well-being. To anticipate and break the path of low literacy across generations, it is necessary to educate the Alpha generation from an early age regarding money and simple patterns of its management. The Alpha generation is expected to be the generation with a better level of financial literacy. A community service activity themed "Introducing Money" for elementary school students was carried out with the aim of introducing money and its wise use from an early age to instill a high sense of responsibility for money. This activity is a form of education that includes an introduction to money, the history of money and the rupiah, an introduction to procedures for treating money according to legal provisions, and simple money management for the Alpha generation. This activity was held at one of the favorite public elementary schools in the city of Tasikmalaya. The activity was carried out in the form of fun learning where students were educated about money and its management through interactive lectures, interesting videos, and interactive games. The participants were 6th grade students of SDN Citapen. This activity has a positive impact on students, as they are able to better understand money and manage it wisely.